Synthesis and Characterization of Citrate-Stabilized Gold-Coated Superparamagnetic Iron Oxide Nanoparticles for Biomedical Applications - René Stein; Bernhard Friedrich; Marina Mühlberger; Nadine Cebulla; Eveline Schreiber; Rainer Tietze; Iwona Cicha; Christoph Alexiou; Silvio Dutz; Aldo R. Boccaccini; Harald Unterweger (Molecules, 2020)
Surface-functionalized gold-coated superparamagnetic iron oxide nanoparticles (Au-SPIONs) may be a useful tool in various biomedical applications. To obtain Au-SPIONs, gold salt was precipitated onto citrate-stabilized SPIONs (Cit-SPIONs) using a simple, aqueous one-pot technique inspired by the Turkevich method of gold nanoparticle synthesis. By the further stabilization of the Au-SPION surface with additional citrate (Cit-Au-SPIONs), controllable and reproducible Z-averages enhanced long-term dispersion stability and moderate dispersion pH values were achieved. The citrate concentration of the reaction solution and the gold/iron ratio was found to have a major influence on the particle characteristics. While the gold-coating reduced the saturation magnetization to 40.7% in comparison to pure Cit-SPIONs, the superparamagnetic behavior of Cit-Au-SPIONs was maintained. The formation of nanosized gold on the SPION surface was confirmed by X-ray diffraction measurements. Cit-Au-SPION concentrations of up to 100 µg Fe/mL for 48 h had no cytotoxic effect on Jurkat cells. At a particle concentration of 100 µg Fe/mL, Jurkat cells were found to take up Cit-Au-SPIONs after 24 h of incubation. A significantly higher attachment of thiol-containing L-cysteine to the particle surface was observed for Cit-Au-SPIONs (53%) in comparison to pure Cit-SPIONs (7%).